2011
DOI: 10.1007/s10880-011-9229-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Depressive and Anxiety Symptoms Among the Caregivers of Leukemic Children

Abstract: This study aims to reveal correlates of depressive and anxiety symptoms among the Turkish caregivers of leukemic children (n = 100). The effects of demographic variables, satisfaction of the basic needs, performance on daily activities, and coping strategies on outcome variables were investigated by hierarchical regression. Accordingly, older age, lower reported income, higher number of other children to be looked after, lower levels of satisfaction of basic needs, and more use of emotion focused coping were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
3
8
1
1
Order By: Relevance
“…The findings of this study suggest that 49% of the parents experience clinically relevant levels of anxiety symptoms and 25% clinically relevant levels of depression symptoms. However, the percentage of depression was lower than that found in the previous study, possibly due to personal positive coping mechanisms. Friends, relatives, and religion have been identified as the most useful sources of coping .…”
Section: Discussioncontrasting
confidence: 93%
“…The findings of this study suggest that 49% of the parents experience clinically relevant levels of anxiety symptoms and 25% clinically relevant levels of depression symptoms. However, the percentage of depression was lower than that found in the previous study, possibly due to personal positive coping mechanisms. Friends, relatives, and religion have been identified as the most useful sources of coping .…”
Section: Discussioncontrasting
confidence: 93%
“…). One study found that lower education was associated with higher depression scores and PTSS up to 1 year post‐diagnosis (Demirtepe‐Saygili & Bozo ; Tremolada et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…; Currier et al . ; Hall ; Liu & Yeh ; Demirtepe‐Saygili & Bozo ; Litzelman et al . ; Masa'Deh et al .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In general, many studies can be found on anxiety, stress, quality of life, and depression of the mothers of children with cancer (Kholasehzadeh et al 2014;Barrera et al 2012;Elcigil & Conk 2010;Demirtepe-Saygılı & Bozo 2011;Bostancı et al 2007;Neu et al 2014;Malpert et al 2015;Chen 2015;Sherief et al 2015). However, considering the culture of parental life in Turkey and the socio-economic status of the mothers, conducting such a study was felt necessary.…”
Section: Plain Language Summarymentioning
confidence: 99%